Possibilities of blossom and twig blight management in organic stone fruit production - Holb, I. J.; Fazekas, M.; Lakatos, P.; Balla, B.; Gáll, J. M. (International Journal of Horticultural Science, 2010)
In this study, possibilities of environmentally-benign plant protection against blossom and twig blight were summarized for organic stone fruit orchards. Symtomps of Monilinia laxa (Aderh. & Ruhl.) Honey) were described and then cultivar susceptibility to blossom and twig blight was discussed. Several sustainable plant protection methods were selected and discussed in details such as mechanical, agrotechnical, biological, and other non-chemical control possibilities (stone powders, plant extracts and restricted chemical materials).